Flebotomi Pada Penyakit Jantung Bawaan Dewasa Sianotik - Nugraha, Ngurah Agung Reza Satria; Susila, I Ketut (PT Kalbe Farma Tbk., 2025)
Adult congenital heart disease is a cardiovascular condition that necessitates a comprehensive approach to medical and surgical intervention. In this condition, cyanosis results from a right-to-left shunt, which subsequently causes secondary erythrocytosis and hyperviscosity. Dehydration and iron deficiency can exacerbate the symptoms of hyperviscosity. One proposed strategy for reducingviscosity is phlebotomy. Phlebotomy procedures should be conducted with adequate fluid replacement to prevent acute stroke. While phlebotomy can reduce red blood cell mass and serum viscosity, it should be performed judiciously and not repeatedly to avoid stroke complications. Repeated phlebotomy without appropriate indications may lead to chronic iron deficiency and microcytic erythrocytes, which paradoxically increase the risk of cerebrovascular complications. Indications for therapeutic phlebotomy include moderate to severe hyperviscosity symptoms with hematocrit levels of at least 65% in the absence of dehydration or iron deficiency.The benefits of phlebotomy should only be considered when appropriate indications are met to achieve improved patient outcomes.